Muhammed B. Ebi'-lfeth El-Ba'li'nin'şerhu Elfiyyeti İbn-i Malik Babu't-Tasrif' adlı eserinin tahkik ve tahlili - Tanta, Anas (My University, 2021)
Bu tez, allame ve fakih vasfının yanı sıra bir nahiv ve dil bilgini olan İmam Şemseddin Muhammed bin Ebi-l Feth el-Ba’lî el-Hanbelî‘nin “Şerh-u Elfiyeti İbni Malik” isimli kitabının sarf bölümünün tahkik ve incelemesinden ibarettir. Kitap “Elfiyetü İbni Malik”in en önemli şerhlerinden birisidir. Zira el-Ba’lî, İbni Malik’in seçkin talebelerinden biridir ve bu şerh el yazması olarak kütüphane raflarında kalmıştır.Tez iki bölümden oluşmaktadır. Birinci bölümde metin tahkik edilmiş, ikinci bölümde ise inceleme ve analiz yapılmıştır.Birinci bölümde eserin el yazması yazıya döküldükten sonra gerekli harekeleme ve numaralandırmalar yapılmıştır. Bu hususta modern imla kurallarına uyulmuş ve gerek el-Ba’lî’nin belirttiği nakiller gerekse metinde yer alan deliller kaynaklarına atfedilmiştir. Kur’an ayetlerinin sure ve ayet numaralarını belirtilmiş, Hadis-i şerifler de tahriç edilmiştir. Şiirlerin sahipleri tespit edilmiş ve meşhur olmayan bilginlerin biyografisine değinilmiştir.İkinci bölümün ilk faslında müellif ve şarihin hayatı ele alınmıştır. Biyografi kitaplarından faydalanılarak müellifin hayatı hakkında bilgi verilmiştir. İkinci fasılda ise; eserin özellikleri, müellifine olan nispeti, önemi ve tahkikinde uygulanan yöntem gibi konulara yer verilmiştir. Üçüncü fasılda el-Ba’lî’nin şerh yöntemi, üslubu, özellikleri ve kaynakları ele alındıktan sonra bu şerh ile İbni Nazım’ın şerhi arasında karşılaştırma yapılmıştır. Buna bağlı olarak el-Ba’lî’nin kendisinden önce gelenlerden ne derece etkilendiği, onlara neler kattığı ve hangi hususlarda onlardan ayrıştığın ve kendisinden sonra gelenler üzerindeki etkisi irdelenmeye çalışılmıştır.

This study aims to manuscript verification the conjugation section from the book (Alfiat Ibn Malik) by Imam Shams al-Din, Muhammad ibn Abi al-Fath al-Baali al-Hanbali, the scholar al-Faqih al-Mufti and the grammatical-linguistic modernist, and this book is one of the most crucial commentaries on Ibn Malik’s millennium because al-Baali is one of Ibn Malik’s special students, when It was still manuscript .The study consists of two parts: the first one is a manuscript verification and the second one is an analytical.The first part, it included manuscript, interviewed it, set the necessary diacritics, and the punctuation, in accordance with modern orthography, and documented the quotes made by Al-Baali, and documented the evidence mentioned in the text. The Quranic verses were attributed, the hadiths of the Prophet were brought out, the poetic verses were attributed to those who said them, and the biographies of unpopular Scholar were investigated.The second part, was inclined studying about the life of the author and commentator in the first chapter. By using scholars’ books about investigation of biographies of flags as a reference, then in the second chapter I studied the manuscript terms of its description and documentation of its attribution to its author and the statement of its importance and value and the methodology used in its manuscripts verfication. Third chapter it was analyzed the Anointion method of Al-Baali describing its style, the most important feature of it, and the sources that He relied on it in saying it, the scholars who were quoted from it, and the most important issues that al-Baali tracked down on Ibn Malik, and a comparison was made between his anointion and that of Ibn al-Nazim, and through it the influence of al-Baali was explained by those who preceded him, and what al-Baali added and was distinguished by it, and its influence on the scholars and commentators who came after him
Keywords: Arap Dili – Şerh- Elfiyye – Tasrif - Muhammed b.Ebu'l-Feth Arabic language; conjugation; Ibn Abi Al- Fath Al-Baali; Ibn Malik; Islam; İslam